How components of ESG performance impact corporate risk-taking? - Sun, Chuanwang; Lu, Shuangji; Zhang, Yaodan (Frontiers in Sustainable Energy Policy, 2024)
Corporate risk-taking (CRT) is crucial for sustainable business development. The focus of this study is to examine the relationship between components of ESG performance (ESGP) and corporate risk-taking. We conduct an empirical analysis using CSI ESG score data of A-share listed companies on the Shanghai and Shenzhen stock exchanges from 2009 to 2022. The conclusions are as follows: (1) ESGP exerts a facilitating effect on CRT. Specifically, environmental performance inhibit CRT, whereas social responsibility and corporate governance performance enhance CRT. (2) The facilitating effect of ESGP on CRT is more pronounced at lower levels of equity concentration. (3) ESGP enhances CRT by increasing the level of innovation and institutional investor shareholding. The contribution of this study is to help firms change CRT by adjusting the components of ESGP.